Fixed-dose combination treatment regimen to control intraocular pressure in glaucoma - V.N. Alekseev; I.R. Gazizova; A.M. Gadzhiev (РМЖ "Клиническая офтальмология")
V.N. Alekseev1, I.R. Gazizova2, A.M. Gadzhiev3 1I.I. Mechnikov North-Western State Medical University, St. Petersburg, Russian Federation 2Institute of Experimental Medicine, St. Petersburg, Russian Federation 3Vsevolozhsk Clinical Inter-district Hospital, Vsevolozhsk, Russian Federation Aim: to assess the efficacy and safety of the treatment with fixed-dose (FDC) and non-fixed-dose combination of latanoprost 0.005% and timolol 0.5% when switching from monotherapy to enhance IOP-lowering effect in primary open-angle glaucoma (POAG). Patients and Methods: 54 patients (93 eyes) with POAG were enrolled in this 4-week study. All patients were subdivided into three groups depending on the treatment regimen. In group I, latanoprost/timolol FDC dosed in the morning (8 A.M.) was prescribed. In group II, latanoprost/timolol FDC dosed in the evening (8 P.M.) was prescribed. In group III, non-FDC of latanoprost 0.005% dosed in the evening (8 P.M.) and timolol 0.5% dosed in the morning (8 A.M.) and in the evening (8 P.M., 15-minute interval to prevent latanoprost from being washed out by timolol) was prescribed. Results: by the end of week 4, in group I, IOP has reduced by 4.2 mm Hg (16.8% from the baseline) when measured at 10 A.M. and by 4.1 mm Hg (16.6% from the baseline) when measured at 4 P.M. In group II, IOP has reduced by 4.6 mm Hg (19.1% from the baseline) when measured at 10 A.M. and by 4.4 mm Hg (18.6% from the baseline) when measured at 4 P.M.caIn group III, IOP has reduced by 3.2 mm Hg (13.6% from the baseline) when measured at 10 A.M. and by 3.3 mm Hg (14.1% from the baseline) when measured at 4 P.M. Interviewing on medication adherence has demonstrated that the average percentage of eye drops taken in time was 63.4% from the required that is lower by 12.7% and 12.2% than in group I and group II, respectively. Conclusion: combination of latanoprost and timolol provides additional IOP lowering in all three groups. Morning instillation of FDC provides additional IOP lowering by 3.2% and 2.5% when measured at 10 A.M. and 4 P.M., respectively, as compared with group III. Evening instillations of FDC provide additional IOP lowering by 5.5% and 4.5% when measured at 10 A.M. and 4 P.M., respectively, as compared with group III. Evening instillations are more beneficial due to the effect on diurnal IOP fluctuations. Our findings demonstrate low rate of adverse side effects. Keywords: glaucoma, POAG, intraocular pressure, fixed-dose combination, prostaglandin analogues, latanoprost, beta-blocker, timolol, Xalacom. For citation: Alekseev V.N., Gazizova I.R., Gadzhiev A.M. Fixed-dose combination treatment regimen to control intraocular pressure in glaucoma. Russian Journal of Clinical Ophthalmology. 2019;19(4):202–205.